2018
DOI: 10.1099/jgv.0.001056
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of activation of the BNLF2a immune evasion gene of Epstein-Barr virus by Zta

Abstract: The human gamma herpes virus Epstein–Barr virus (EBV) exploits multiple routes to evade the cellular immune response. During the EBV lytic replication cycle, viral proteins are expressed that provide excellent targets for recognition by cytotoxic T cells. This is countered by the viral BNLF2a gene. In B cells during latency, where BNLF2a is not expressed, we show that its regulatory region is embedded in repressive chromatin. The expression of BNLF2a mirrors the expression of a viral lytic cycle transcriptiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…We therefore tested whether exogenous expression of IRF4 in DG75 cells can activate miR-155HG transcription via upstream enhancers. Because IRF4 activates the control plasmid (pRL-TK), firefly reporter activity was normalized to actin expression as a previously described alternative in these assays ( 36 ). Consistent with previously reported data, we found that the exogenous expression of IRF4 resulted in a 4-fold increase in miR-155HG promoter activity ( 28 ).…”
Section: Resultsmentioning
confidence: 99%
“…We therefore tested whether exogenous expression of IRF4 in DG75 cells can activate miR-155HG transcription via upstream enhancers. Because IRF4 activates the control plasmid (pRL-TK), firefly reporter activity was normalized to actin expression as a previously described alternative in these assays ( 36 ). Consistent with previously reported data, we found that the exogenous expression of IRF4 resulted in a 4-fold increase in miR-155HG promoter activity ( 28 ).…”
Section: Resultsmentioning
confidence: 99%
“…We therefore tested whether exogenous expression of IRF4 in DG75 cells can activate miR-155HG transcription via upstream enhancers. Because IRF4 activates the control plasmid (pRL-TK), Firefly reporter activity was normalized to actin expression as a previously described alternative in these assays (35). Consistent with published data, we found that exogenous expression of IRF4 resulted in a 4-fold increase in miR-155HG promoter activity (29).…”
Section: Resultsmentioning
confidence: 99%
“…For instance, BNLF2a is a vital EBV inhibitor of the transporter associated with antigen processing (TAP) protein complex. It can shut down peptide/HLA presentation through the blockage of peptides and ATP binding to the TAP complex [ 70 ]. The third evasion molecule is an EBV-encoding gene, BILF1, which encodes a constitutively active G-protein-coupled receptor (GPCR) that not only downregulates HLA I via endocytic and exocytic pathways, but also induces signalling-mediated tumourigenesis [ 71 ].…”
Section: Specific Immune Response To Ebvmentioning
confidence: 99%